ACCOUNTING INNOVATION MANAGEMENT - Sviatoslav Katerinin (Вестник Северо-Кавказского федерального университета)
Innovation activity at the present rate of development needs in accounting management. To this end, we developed a system of accounting innovation management organization, which set the goal (property management), defined information base (structured plan accounts) designed tools (derivatives system balance sheet), and to predict the expected results.